Comparison of Miniaturized Raman Spectrometers for Discrimination of Carotenoids of Halophilic Microorganisms - Jehlička, Jan; Culka, Adam; Mana, Lily; Oren, Aharon (Frontiers in Microbiology, 2019)
We present a comparison of the performance of four miniature portable Raman spectrometers for the discrimination of carotenoids in samples of carotene-producing microorganisms. Two spectrometers using a green laser allowing to obtain Resonance Raman (or pre-Resonance Raman) signals, one instrument with a 785 nm laser, and a recently developed Portable Sequentially Shifted Excitation Raman spectrometer (PSSERS) were used for identifying major pigments of different halophilic (genera Halobacterium, Halorubrum, Haloarcula, Salinibacter, Ectothiorhodospira, Dunaliella) and non-halophilic microorganisms (Micrococcus luteus, Corynebacterium glutamicum). Using all the tested instruments including the PSSERS, strong carotenoids signals corresponding to the stretching vibrations in the polyene chain and in-plane rocking modes of the attached CH3 groups were found at the correct positions. Raman spectra of carotenoids can be obtained from different types of microbiological samples (wet pellets, lyophilized cultur biomass and pigment extracts in organic solvents), and can be collected fast and without time-consuming procedures.